ENGLAND, PORTUGAL AND THE SILVER RIVER IN THE CENTURY. XIX: RELATIONS AND CONFLICTS. - Colvero, Ronaldo Bernardino (Revista de Historia Social y de las Mentalidades, 2021)
The arrival of the Portuguese royal family to Brazil in 1808, resulted in a new configuration of political and trade relations, especially between Portugal and England, in colonial Brazil. The project to join together the Iberian domains in Latin America under the princess's figure of Carlota Joaquina, represented an example of this practice. While this political and administrative blending of American colonial possessions, especially in the Plata region, did not consolidate, it could be noticed the power of influence and contradictions of interests, that England, through their representatives, executed, under the Iberian leaders, in order to maximize their earnings, especially the commercial ones.
Keywords: Colonial America; English Influence; Power; Prata Region